Antiviral activity of the natural alkaloid anisomycin against dengue and Zika viruses - Quintana, Verónica Mara (2020)
Flaviviruses constitute a public health concern because of their global burden and the lack of specific antiviral treatment. Here we investigated the antiviral activity of the alkaloid anisomycin against dengue (DENV) and Zika (ZIKV) viruses. At non-cytotoxic concentrations, anisomycin strongly inhibited the replication of reference strains and clinical isolates of all DENV serotypes and Asian and African strains of ZIKV in Vero cells. Anisomycin also prevented DENV and ZIKV multiplication in human cell lines. While initial steps of DENV and ZIKV replicative cycle were unaffected, a high inhibition of viral protein expression was demonstrated after treatment with anisomycin. DENV RNA synthesis was strongly reduced in anisomycin treated cultures, but the compounddid not exert a direct inhibitory effect on 2′ O-methyltransferase or RNA polymerase activities of DENV NS5 protein. Furthermore, anisomycin-mediated activation of p38 signaling was not related to the antiviral action ofthe compound. The evaluation of anisomycin efficacy in a mouse model of ZIKV morbidity and mortality revealed that animals treated with a low dose of anisomycin exhibited a significant reduction in viremia levels anddied significantly later than the control group. This protective effect was lost at higher doses, though. In conclusion, anisomycin is a potent and selective in vitro inhibitor of DENV and ZIKV that impairs a post-entry step of viral replication; and a low-dose anisomycin treatment may provide some minimal benefit in a mouse model.